Methodologies for the inclusive education of students with severe visual impairment or blindness / Metodologías que garantizan la inclusión educativa de estudiantes con discapacidad visual grave o ceguera. Issue 2 (2nd April 2016) - Serrano, Isabel; Palomares, Ascensión; Kostich, Catherine
Abstract: The aim of this paper is to present the educational experiences that have been implemented in the community of Madrid (Spain) with students with severe visual impairment or blindness. We highlight why and how the new educational policies being implemented have achieved the genuine inclusion of these students in line with European educational objectives. The study was carried out during the academic years 2010–11 to 2015–16. We conclude that the educational inclusion of students with visual impairment becomes a reality upon the effective participation of two specialized teams, namely, the educational psychologists for young children (divided in stages from zero to three years and from four to 12 years of age) and the educational specialists in visually impaired children. This constitutes a prime example that can be extended to other contexts and other disabilities. It becomes evident that, to be effective, inclusive education requires a joint and coordinated response from all professionals involved in the education process.